ORDER OF OPERATIONS USING PEMDAS WORKSHEET

PEMDAS rule can be used to simplify complicated  numerical expressions with more than operations.

Very simply way to remember PEMDAS rule!

----> Parentheses

E ----> Exponent 

M ----> Multiplication

D ----> Division

----> Addition

----> Subtraction

Problem 1 :

a)  (5 - 2)- 6

b)  3 × 4 + 52

c)  4 × 3- (3 + 2)2

d)  3 - 22 ÷ 2 + 1

e)  (5 - 2)- 22

f)  (15 - 32) ÷ 3

g)  5 × 2+ 2 × 32

h)  5 × (22 + 2) + 6

i)  35 - 3 × 2+ 7

Solution :

a)

= (5 - 2)- 6

3- 6

= 9 - 6

= 3

Parentheses

Exponent

Subtraction

b)

= 3 × 4 + 52

= 12 + 25

= 37

Exponent

Addition

c)

 = 4 × 3- (3 + 2)2

4 × 3- 52

= × 9 - 25

= 36 - 25

= 11

Parentheses

Exponent

Multiplication

Subtraction


d)

 = 3 - 22 ÷ 2 + 1

= 3 - ÷ 2 + 1

= 3 - 2 + 1

= 3 - 1

= 2

Exponent

Division

Addition

Subtraction

e)

= (5 - 2)- 22

= 32  22

= 9 - 4

= 5

Parentheses

Exponent

Subtraction

f)

= (15 - 32) ÷ 3

= 15 - ÷ 3

 = 15 - 3

= 12

Parentheses, Exponent

Division

Subtraction

g)

= 5 × 2+ 2 × 32

= × 4 + × 9

= 20 + 18

= 38

 Exponent

Multiplication

Addition

h)

= 5 × (22 + 2) + 6

= × 6 + 6

= 30 + 6

= 36

Parentheses, Exponent

Multiplication

Addition

i)

= 35 - 3 × 2+ 7

=35 - 3 × 8 + 7

=35 - 24 + 7

= 35 - 17

= 18

Exponent

Multiplication

Addition

Subtraction

Problem 2 :

Replace * with either +, -, ×, ÷ or ÷ to make a true statement :

a)  (18 * 2) ÷ 10 = 2

b)  (10 * 3) * 7 = 1

c)  15 * 3 + 2 * 5 = 15

Solution :

a)

 (18 * 2) ÷ 10 = 2

By replacing * as +, we get

(18 + 2) ÷ 10 = 2

20 ÷ 10 = 2

2 = 2 (true)

b)

(10 * 3) * 7 = 1

By replacing * as -, we get

(10 - 3) * 7 = 1

* 7 = 1

By replacing * as ÷, we get

÷ 7 = 1

1 = 1 (true)

c)

 15 * 3 + 2 * 5 = 15

By replacing * as ÷, we get

 15 ÷ 3 + 2 * 5 = 15

5 + 2 * 5 = 15

By replacing * as ×, we get

5 + × 5 = 15

5 + 10 = 15

15 = 15 (true)

Problem 3 :

Insert brackets into the following to make them true :

a)  8 + 4 ÷ 2 + 2 = 3

b)  5 + 3 × 6 - 10 = 38

c)  13 + 5 ÷ 5 + 4 = 2

Solution :

a)

8 + 4 ÷ 2 + 2 = 3

(8 + 4) ÷ (2 + 2) = 3

12 ÷ 4 = 3

3 = 3 (true)

b)

5 + 3 × 6 - 10 = 38

  (5 + 3) × 6 - 10 = 38

8 × 6 - 10 = 38

48 - 10 = 38

38 = 38 (true)

c)

13 + 5 ÷ 5 + 4 = 2

(13 + 5) ÷ (5 + 4) = 2

18 ÷ 9 = 2

2 = 2 (true)

Apart from the stuff given above if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

Recent Articles

  1. Trigonometry Word Problems Worksheet with Answers

    Jan 17, 22 10:45 AM

    Trigonometry Word Problems Worksheet with Answers

    Read More

  2. Trigonometry Word Problems with Solutions

    Jan 17, 22 10:41 AM

    Trigonometry Word Problems with Solutions

    Read More

  3. Writing Numbers in Words Worksheet

    Jan 16, 22 11:56 PM

    Writing Numbers in Words Worksheet

    Read More